Scattering strength at active volcanoes in Japan as inferred from the peak ratio analysis of teleseismic P waves - Gugi Ganefianto (SpringerOpen, 2021)
Abstract Small-scale seismic velocity heterogeneity has been studied through the calculation of peak amplitude ratio as a means to quantify the strength of seismic wave scattering at volcanoes in Japan. This ratio is defined as the ratio of the maximum (peak) P wave energy in the transverse component seismogram envelope over that of the three-component sum seismogram envelope (transverse + radial + vertical). According to the previous study using Japan’s Hi-net seismometer network, the peak ratio is observed to be larger near the (active) quaternary volcanoes. However, these Hi-net stations are not positioned on the volcanoes themselves. This study systematically examines the peak ratios at 47 active volcanoes across Japan, using seismometers operated by the Japan Meteorological Agency (JMA). Analyses were performed at four frequency bands: 0.5–1, 1–2, 2–4, and 4–8 Hz. We found that the JMA stations yield higher peak ratios than the Hi-net stations. Their differences are statistically significant at the 99.9% confidence level in all frequency bands. We also examined the differences between the ground surface and borehole stations of the JMA network. The former shows larger peak ratios, and for most frequency bands, the differences are also statistically significant at the 99.9% confidence level. This suggests an intensification of small-scale medium heterogeneities especially at shallow depths at active volcanoes, and that scattering might have been enhanced at the very shallow parts. Graphical Abstract